Arquitetura da informação nos aplicativos iFood e 99 Food - Pereira, Larissa Beatriz de Lima (Brasil, 2023)
The present work, is correlated to the user and the information, and had as principle the concepts of the architecture of the information. The objective was to understand the importance of accessibility, usability in applications. Regarding the methodology, it was supported by the structured and comparative analysis of the applications, namely: iFood and 99 Food. The analysis was based on information architecture criteria for digital applications in order to improve access to information. In the comparative process of the applications, we highlight the applications in the APPs, through the similarities and differences. Thus, the analysis of the applications allowed us to understand which structures were essential for the user to succeed in finding what he needed efficiently and effectively, as well as identifying points of improvement in the applications. Thus, the information architecture favored and contributed to the process of user interaction with digital environments.